2014
DOI: 10.1007/s00726-014-1762-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis of amino acid and energy metabolism in rats supplemented with chlorogenic acid

Abstract: This study was conducted to investigate effects of chlorogenic acid (CGA) supplementation on serum and hepatic metabolomes in rats. Rats received daily intragastric administration of either CGA (60 mg/kg body weight) or distilled water (control) for 4 weeks. Growth performance, serum biochemical profiles, and hepatic morphology were measured. Additionally, serum and liver tissue extracts were analyzed for metabolomes by high-resolution 1H nuclear magnetic resonance-based metabolomics and multivariate statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 81 publications
(93 reference statements)
2
24
0
Order By: Relevance
“…In the present study, supplementation of LJE at doses of 1 and 2 g/kg DM reduced both NEFA and BHBA concentrations in blood. Previous study has demonstrated that supplemen tation with chlorogenic acid regulated energy metabolism and decreased serum BHBA concentration in rats [22]. More over, LJE supplementation increased the intake of the cows in the current study, therefore reduced the concentrations of NEFA and BHBA by alleviating the mobilization of adipose tissue.…”
Section: Biomarkers Of Energy Metabolismsupporting
confidence: 54%
“…In the present study, supplementation of LJE at doses of 1 and 2 g/kg DM reduced both NEFA and BHBA concentrations in blood. Previous study has demonstrated that supplemen tation with chlorogenic acid regulated energy metabolism and decreased serum BHBA concentration in rats [22]. More over, LJE supplementation increased the intake of the cows in the current study, therefore reduced the concentrations of NEFA and BHBA by alleviating the mobilization of adipose tissue.…”
Section: Biomarkers Of Energy Metabolismsupporting
confidence: 54%
“…EU has been reported to promote the generation of Ser, Glu and Lys in the muscle of chickens (Wang et al, ). CGA was confirmed to increase serum Gly level and liver glutathione level of rats (Ruan et al, ) and increase the TEAA and TAA levels in grass carp (Sun et al). The present study showed that the supplementation of CGA, GP and active compound mixture significantly increased TAA in muscle based on dry matter ( p < 0.05).…”
Section: Discussionmentioning
confidence: 88%
“…SOD and GSH-Px are two major antioxidant enzymes to scavenge the excessive internal reactive oxygen species (ROS) which exert radical-mediates damages to biological macromolecules (proteins, lipids and DNA) [42] , therefore the activities of SOD and GSH-Px are plausibly regarded as a mark reflecting redox of organism [15] . In this study, compared with the control group, mold-contaminated feed significantly decreased T-SOD activity (P<0.05) and GSH-Px activity (P>0.05) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-seven amino acids were detected in serum based on our previous study [42] – [43] via LC-MS/MS (HPLC Ultimate3000 and 3200 Q TRAP LC-MS/MS): L-arginine, L-histidine, L-isoleucine, L-leucine, L-lysine, L-phenylalanine, L-methionine, L-threonine, L-tryptophan, L-valine, glycine, L-serine, L-tyrosine, L-asparagine, L-aspartic acid, L-citrulline, L-glutamic acid, L-glutamine, L-ornithine, L-cystine, L-homocystine, L-alanine, L-carnosine, hydroxy-L-proline, 1-methyl-L-histidine, 3-methyl-L-histidine, and L-proline.…”
Section: Methodsmentioning
confidence: 99%